Resolving the abundance and air-sea fluxes of airborne microorganisms in the North Atlantic Ocean - Mayol, Eva; Jiménez, María A.; Herndl, Gerhard J.; Duarte, Carlos M.; Arrieta, Jesús M. (Frontiers in Microbiology, 2014)
Airborne transport of microbes may play a central role in microbial dispersal, the maintenance of diversity in aquatic systems and in meteorological processes such as cloud formation. Yet, there is almost no information about the abundance and fate of microbes over the oceans, which cover >70% of the Earth’s surface and are the likely source and final destination of a large fraction of airborne microbes. We measured the abundance of microbes in the lower atmosphere over a transect covering 17° of latitude in the North Atlantic Ocean and derived estimates of air-sea exchange of microorganisms from meteorological data. The estimated load of microorganisms in the atmospheric boundary layer ranged between 6×104 and 1.6×107 microbes per m2 of ocean, indicating a very dynamic air-sea exchange with millions of microbes leaving and entering the ocean per m2 every day. Our results show that about 10% of the microbes detected in the boundary layer were still airborne 4 days later and that they could travel up to 11,000 km before they entered the ocean again. The size of the microbial pool hovering over the North Atlantic indicates that it could play a central role in the maintenance of microbial diversity in the surface ocean and contribute significantly to atmospheric processes.